The Rise of Ethnic Politics in Latin America - Madrid, Raúl L. (Cambridge University Press, 2012)
The Rise of Ethnic Politics in Latin America explores why indigenous movements have recently won elections for the first time in the history of the region. Raúl L. Madrid argues that some indigenous parties have won by using inclusive populist appeals to reach out to whites and mestizos. Indigenous parties have managed to win support across ethnic lines because the long history of racial mixing in Latin America blurred ethnic boundaries and reduced ethnic polarization. The appeals of the indigenous parties have especially resonated in the Andean countries because of widespread disenchantment with the region's traditional parties. The book contains up-to-date qualitative and quantitative analyses of parties in seven countries, including detailed case studies of Bolivia, Ecuador and Peru.